Hubungan Antara Tekanan Darah Dan Ukuran-Ukuran Anthropometrik Sekelompok Anak sekolah Dasar di Daerah Istimewa Yogyakarta - A. Samik Wahab, A. Samik Wahab (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1985)
The relationship between blood pressure and body weight, body height and upper arm circumference was studied in 506 school children, consisting of 227 boys and 279 girls, aged 6-14 years. Blood pressure was measured by using mercury sphygmomanometer. measurements were conducted once in the sitting position, and the subjects were selected at random from 7 000 school children in the district of Sewon, Bantul, Yogyakarta. The results found showed that there are correlations between either systolic or diastolic blood pressure with body weight, body height and upper arm cir cumference, especially in the ages of 15 co 14 years. Key Words: blood pressure - anthropometric measurements - school children - nutrition Ã¢â¬âbody mass